ICT Based Innovations Proceedings of CSI 2015 - Saini, A. K.; Nayak, A. K.; Vyas, Ram Krishna; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This volume comprises the select proceedings of the annual convention of the Computer Society of India. Divided into 10 topical volumes, the proceedings present papers on state-of-the-art research, surveys, and succinct reviews. The volumes cover diverse topics ranging from communications networks to big data analytics, and from system architecture to cyber security. This volume focuses on ICT Based Innovations. The contents of this book will be useful to researchers and students alike.
FPKIVS- A Stellar Approach to Voting Systems in India -- Minimax (Maximin) with Special Approach of Gamification in Higher Education -- Comparing the Behavior of Oversampling and Undersampling Approach of Class Imbalance Learning by Combining Class Imbalance Problem with Noise -- Proposed ICT Based Transportation Model: EEG -- Multi-Criteria Rating Using Fuzzy Ranking for Improving Soil Recommendation System -- Design and Development of the Agricultural Model: a way to Connect Farmer Community to Agriculture Market for Betterment of Rural Development -- A Methodical Study on Behaviour of Different Seeds Using an Iterative Technique with Evaluation of Cluster Validity -- BharataNatyam Dance Classification with Rough Set Tools -- Effective & Efficient Digital Advertisement Algorithms -- Automation of Patient Information in Healthcare System -- Recommendation for Selecting Smart Village in India Through Opinion Mining Using Big Data Analytics -- Analyzing Online Groups or the Communities in Social Media Networks by Algorithmic Approach -- Open Source EJBCA Public Key Infrastructure for e-Governance Enabled Software Systems in RRCAT -- Anticipation of Gross Domestic Product Using World Development Indicators -- An Efficacious Matching of Finger Knuckle Print Images Using Gabor Feature -- An Ensemble Based Decision Support System for the Students' Academic Performance Prediction -- Adding Big Value to Big Businesses: A Present State-of-the-Art of Big Data, Frameworks and Algorithms -- Content Based Social Network Aggregation -- Collaborative Filtering Based Recommender System -- Classifying Exoplanets as Potentially Habitable Using Machine Learning -- Model to Detect Fake Reviews in Tourism Sector -- Towards Understanding Preference of Use of Emoticons for Effective Online Communication and Promotion: A Study of National Capital Region of Delhi, India -- Analysis of Functional Parameters to Implement Knowledge Management for Sustainable e-Governance in Agriculture Sector of Saurashtra Regionof Gujarat State -- Trust and Distrust in Web: Two Sides of a Same Coin or Poles Apart? -- Computer Simulation Using GPSC Package Matlab, Simulink for Bioinformatics Professional.
Keywords: Computer networks .; Telecommunication; Computer Communication Networks; Communications Engineering, Networks